Jahrbuch Migration und Gesellschaft / Yearbook Migration and Society 2022/2023 Focus: »Climate« - Peterlini, Hans Karl; Donlic, Jasmin (Jahrbuch Migration und Gesellschaft / Yearbook Migration and Society, 2023)
Migration is not a state of emergency, but a basic existential experience of humanity. It shapes contemporary societies by challenging established orders, creating transnational spaces beyond national hegemonies, creating new economies, influencing urban and communal ways of life, making inequality and precariousness visible locally and globally. Migration research as a social science does not narrow the focus to 'the migrants', but investigates the conditions for living together and shaping life between ethnicization and pluralization, discrimination and empowerment, division and participation. The Yearbook Migration and Society repeatedly turns the prism of narrative anew. The 2022/2023 edition focuses on the topic »Climate«.